2018 World Symposium on Digital Intelligence for Systems and Machines (DISA) 2018
DOI: 10.1109/disa.2018.8490612
|View full text |Cite
|
Sign up to set email alerts
|

Improving Presentation Skill Through Gamified Application - Gamification in Practice

Abstract: Gamification has been used for many years, as a major factor to enhance user's engagement in non-game context. This study focuses on design of an online peer support application to improve presentation skills among young unemployed users. Furthermore, the gamification principles such as pointing system and leaderboard panel are integrated into the design to encourage users for different activities. Remote test is conducted with 47 test subjects to investigate their attitudes toward gamification elements in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…On the other hand, internet development leads people into the online method including in the training of presentation. The result of the study that focuses on the design of an online peer support application to improve presentation skills among young unemployed users shows that online training can be used by the student (Leinonen, Haapaniemi, Mattila, Firouzian & Pulli, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, internet development leads people into the online method including in the training of presentation. The result of the study that focuses on the design of an online peer support application to improve presentation skills among young unemployed users shows that online training can be used by the student (Leinonen, Haapaniemi, Mattila, Firouzian & Pulli, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, game-based apps can also be used for presentation evaluation [53]. In order to promote evaluation, these gamification concepts also feature an integrated pointing system and leaderboard panels [54].…”
Section: Evaluating Presentations In Online Learningmentioning
confidence: 99%
“…In addition, in a presentation activity that has been conducted by Leinonen et al (2018), they have found that gamification features that have been incorporated as one learning platform to improve presentation skills do not show positive results. The respondents perhaps like the idea that the tool is easy to use but they are not interested so much in applying the tool to improve their presentation.…”
Section: Statement Of Problemmentioning
confidence: 99%